Eficiência fotossintética de plantas de arroz infectadas por Curvularia lunata (Wakker) Boedijn Meyerno - Dias, Carlos Wendell Soares (2018)
Among the factors that decrease rice crop productivity, phytosanitary problems arising from fungal diseases are potentially causing loss worldwide. The leaf spot associated with Curvularia lunata has only been reported in Brazil and India, and has become common in the rice fields of the State of Maranhão. Knowing the damage that this disease can cause both in phenology and in the physiology of rice plants is essential to develop, if necessary, control strategies. The objective of this study was to evaluate the development of leaf spot disease as a function of different numbers of inoculations with C. lunata and physiological variables in rice plants. The experiment was conducted in a greenhouse, using a 2x6 factorial scheme, with two varieties (BRS Primavera and IRGA 424), six treatments, two controls, one absolute (without fertilization - T0), one relative (T1), plants with one inoculation, two inoculations, three inoculations and four inoculations (T2, T3, T4 and T5) and five replications. There were no statistical differences between the varieties when evaluating the injured area and number of lesions. When the number of lesions was evaluated, the BRS Primavera variety showed the highest amount of IRGA 424, although the leaf severity was higher in the IRGA 424 variety. The T5 Treatment showed a significant difference in relation to the others in all evaluated phytosanitary parameters. No significant differences were found between treatments T2, T3 and T4 regarding the injured area, number of lesions and leaf severity. With regression analysis, a highly significant positive linear correlation (p < 0.001) was observed in the two varieties studied between leaf spot severity and leaf spot severity caused by C. lunata. As regards the physiological parameters, variations of the photosynthetic index between the treatments of the variety IRGA 424, similar behavior to the density of reaction center per molecule of chlorophyll (RC / ABS) were observed. The regression analysis between stomatal conductance and the Ball-Berry Index showed a very significant positive linear correlation (p < 0.01) in the Primavera variety. IRGA 424 showed a highly significant positive exponential correlation (p < 0.001). As for the photosynthetic CO2 assimilation, the mean values of IRGA 424 treatments with three and four inoculations and higher severity (T4 and T5) had an increase in photosynthetic assimilation of CO2 higher than the other treatments (2.14 and 2.46 mol-2s -1) and higher still in the comparison between varieties in the same treatments, which raises the need for further studies to clarify the mechanisms associated with these results.